Mechanisms of resistance in bacteria: an evolutionary approach. - Amaral, Leonard (2021)
Acquisition of resistance is one of the major causes of failure in therapy of bacterial infections. According to the World Health Organization (WHO), thousands of deaths caused by Salmonella sp., Escherichia coli, Staphylococcus aureus or Mycobacteria tuberculosis are due to failure in therapy caused by resistance to the chemotherapeutic agents. Understanding the mechanisms of resistance acquisition by the bacterial strains is therefore essential to prevent and overcome resistance. However, it is very difficult to extrapolate from in vitro studies, where the variables are far less and under constant control, as compared to what happens in vivo where the chosen chemotherapeutic, its effective dose, and the patient's immune system are variables that differ substantially case-by-case. The aim of this review is to provide a new perspective on the possible ways by which resistance is acquired by the bacterial strains within the patient, with a special emphasis on the adaptive response of the infecting bacteria to the administered antibiotic.